KIR2DL2 enhances protective and detrimental HLA class I-mediated immunity in chronic viral infection. - Nafisa-Katrin Seich Al Basatena; Aidan Macnamara; Alison M Vine; Chloe L Thio; Jacquie Astemborski; Koichiro Usuku; Mitsuhiro Osame; Gregory D Kirk; Sharyne M Donfield; James J Goedert; Charles R M Bangham; Mary Carrington; et al. (PLoS Pathogens)
Killer cell immunoglobulin-like receptors (KIRs) influence both innate and adaptive immunity. But while the role of KIRs in NK-mediated innate immunity is well-documented, the impact of KIRs on the T cell response in human disease is not known. Here we test the hypothesis that an individual's KIR genotype affects the efficiency of their HLA class I-mediated antiviral immune response and the outcome of viral infection. We show that, in two unrelated viral infections, hepatitis C virus and human T lymphotropic virus type 1, possession of the KIR2DL2 gene enhanced both protective and detrimental HLA class I-restricted anti-viral immunity. These results reveal a novel role for inhibitory KIRs. We conclude that inhibitory KIRs, in synergy with T cells, are a major determinant of the outcome of persistent viral infection.